The influence of NOx, temperature, wind and total radiation on the level of ozone concentration in the Upper Silesian agglomeration - Kobza, Joanna; Dul, Lechosław; Geremek, Mariusz (Frontiers in Public Health, 2024)
In 2019, ozone was responsible for about 365,000 premature deaths worldwide (6.21 million healthy life years lost) and acute ozone exposure led to 16,800 premature deaths in the European Union. The aim of the study was to estimate the influence of NO, NO2, wind direction (WD) wind speed (WS), air temperature (TA), and total radiation (GLR) on ozone concentration levels. Data provided by 3 automatic air quality monitoring stations of the Regional Environmental Protection Inspectorate in Katowice, were used in this study. The measurements were conducted in from January 1 2009 to December 31 2017. The data obtained from the measuring stations were statistically analysed. The study showed that the strongest influencing factors for O3 values are air temperature and total radiation, with each showing a high correlation with ozone concentration. NO and NO2 had a dual effect on O3 concentration, causing an increase in ozone concentration at low NO and NO2 concentrations and a decrease in ozone concentration at higher NO and NO2 concentrations. We noted that the direction of the wind had very little effect on the concentration of O3. The influence of wind speed on the O3 level was also small, but stronger than that of the wind direction. The research shows that in the analysed years for selected measuring stations the strongest factors influencing O3 concentration are air temperature and total radiation, the NO and NO2 concentrations had a dualistic effect on the O3 concentration.